Martin Luther: 'n Inleiding tot sy lewe, denke en geskrifte - van Wyk, Ignatius W.C. (Natie) (HTS Teologiese Studies / Theological Studies Supplement, 2019)
In 2017 the world celebrated the 500 years of the Reformation of the 16th century. Martin Luther was at the centre of this jubilee. He is the father of the Protestant Church. A large section of the Afrikaans-speaking community in southern Africa (and those scattered all over the world) belong to one of the Protestant churches. There is not a single academic introduction on Luther in Afrikaans. This publication will be the first in Afrikaans on Luther. The purpose is also to introduce the well-known and unknown writings of Luther to students and lecturers. Most readers will for the first time be able to read passages from his letters, sermons and commentaries. This book will hopefully be the beginning of a southern African Luther-reception. This will be a major contribution to the South African scholarship on church history. It will be the first publication that offers biographical information as well as information on and translations of his writings. Luther has until now, not spoke Afrikaans.The book is written from a southern African perspective. The author is looking for answers on African problems and challenges from Luther. Many of Luther's writings are relevant to our situation. He (as one example) urged the authorities and parents to ensure education for all children. In this country thousands of children are not in school, or do not complete their schooling education. Although we are centuries apart, we could still learn from Luther in this regard. Specialists in church history and systematic theology, as well as ministers and students. Hopefully this book will become prescribed literature at faculties of theology and seminars. The universal-accepted methodologies in the writing of church history are followed. One of the unique features of this book is the translations into Afrikaans of all quotations from Medieval German and Latin. This has never been done previously.